Targeted Isolation of Two New Anti-inflammatory and UV-A Protective Dipyrroloquinones from the Sponge-associated Fungus Aspergillus tamarii MCCF102 - Niveditha, Lekshmi; Fu, Peng; Leao, Tiago F.; Li, Te; Wang, Tingting; Poulin, Remington X.; Gaspar, Lorena R.; Naman, C. Benjamin; Thavarool Puthiyedathu, Sajeevan (Planta Medica, 2022)
In following up on observed in vitro anti-inflammatory activity of the organic extract of the marine sponge-derived fungus Aspergillus tamarii MCCF102, two new dipyrrolobenzoquinones, terreusinone B and C (1 and 2), were discovered along with the known analogue, terreusinone (3). The structures of 1–3 were determined by spectroscopic and spectrometric analyses, along with chemical inter-conversion. In vitro testing on lipopolysaccharide (LPS) stimulated RAW 264.7 murine macrophage cells revealed that 1–3 exhibit anti-inflammatory activity by inhibiting nitric oxide production in a dose-dependent manner (IC50 < 1 µM) without any cytotoxicity observed at the same concentrations. Due to this and the UV-A absorptive properties imparted by the highly conjugated structures of these molecules, the potential for using 1–3 or related analogues as natural sunscreen components is suggested. Gene sequencing and informatics biosynthetic gene cluster comparisons were insufficient to confidently elucidate the biosynthetic origins of these compounds, possibly suggesting the occurrence of a gene cluster not detected in the initial sequencing or a non-canonical pathway that should be further investigated.
Keywords: Aspergillus tamarii; sponge-associated fungi; terreusinone; dipyrroloquinone; anti-inflammatory; sunscreen